The strange case of Dr. Jekyll and Mr. Hyde - Stevenson, Robert Louis, 1850-1894 (New York : Dover Publications, 1991)
Fiction.
Keywords: Multiple personality -- Fiction; London (England) -- Fiction; Self-experimentation in medicine -- Fiction